Study the antioxidant of phenol compounds isolated from black tea Camellia Sinensis L. in male rats exposed to methotrexate - Hassan, Walaa Salih; Rabee, Doaa Adil; Atallah, Aqeel H.; Al-Kaykanee, Ahmed; Jassim, Yazi Abdullah (Edelweiss Applied Science and Technology, 2025)
This study aims to comprehend the function of phenolic compounds and black tea (Camellia sinensis L.) against oxidative stress brought on by methotrexate medication overdose in male rats. The study used 60 adult male rats, and groups of eight rats were formed. T1: 0.85% Normal saline (control). T2: phenol (75 mg/kg body weight) + methotrexate (10 mg/kg). T3: 125 mg/kg phenol with 10 mg/kg methotrexate. T4: 150 mg/kg phenol with 10 mg/kg methotrexate injection. T5: injection: 200 mg/kg black tea + 10 mg/kg methotrexate. T6: Methotrexate 10 mg/kg + 250 mg/kg black tea injection. T7: 300 mg/kg black tea injection + 10 mg/kg. T8: Methotrexate treatment, 10 mg/kg body weight. Blood samples were taken 30 times a day for 14 days after oral dosing. The total protein, blood sugar, hepatic enzyme efficiency, lipid peroxidation, and glutathione peroxidation of male rats were measured. The results indicated that treated black tea and phenol isolated from black tea showed that MDA and LPO concentrations were significantly higher in T8 rats than in T1 rats treated with methotrexate. With drinking water, methotrexate increases ROS and oxidative stress, raising liver tissue MDA and LPO levels and lowering GPX. In male rats, injections of 300 and 125 mg/kg of phenol and phenol extracts prevent and reduce oxidative stress caused by methotrexate by increasing protein and GPX levels and decreasing blood sugar, MDA, and LPO levels in liver tissue.